Evaluation of efficiency of precision irrigation for potatoes - J. Jobbágy; J. Simoník; P. Findura (Research in Agricultural Engineering, 2011)
The objective of the presented paper was to verify in practice the methods of precision irrigation, defined theoretically, under the employment of reel hose irrigation machines. The surface area of the field was 22 ha. The basic soil hydrological coefficients were measured in 19 monitoring points, specifically the field capacity and the wilting point. The field capacity ranged between 28.83% and 32.11% by vol., and the wilting point was in the interval between 8.40% and 12.40% by vol. At the conclusion, the soil moisture as a factor decisive for determining the irrigation rate was measured in these monitoring points. The irrigation rate ranged from 0 to 40 mm for the specific date of the soil moisture determination. During the whole growing season, five irrigation rates were applied according to the principles of precision irrigation. As compared to conventional water application, precision irrigation contributed to water saving in the amount of 478.56 m3/ha. The electric power saving reached 249.68 kWh/ha. The cost saving was characterised by the value of 9.1 EUR/ha and this represented 23.8%. The results have shown that precision irrigation is a fully effective system of precision farming, although the procurement and implementation of new technology and software requires at first a significant financial cost. There is also an increased need for the education and skills of the operating staff.